2016
DOI: 10.1093/infdis/jiw047
|View full text |Cite
|
Sign up to set email alerts
|

Declining Effectiveness of Herpes Zoster Vaccine in Adults Aged ≥60 Years

Abstract: Understanding long-term effectiveness of herpes zoster (HZ) vaccine is critical for determining vaccine policy. 176 078 members of Kaiser Permanente ≥60 years vaccinated with HZ vaccine and three matched unvaccinated members were included. Hazard ratios and 95% confidence intervals (CIs) associated with vaccination at each year following vaccination were estimated by Cox regression model. The effectiveness of HZ vaccine decreased from 68.7% (95% CI, 66.3%-70.9%) in the first year to 4.2% (95% CI, -24.0% to 25.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
109
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(114 citation statements)
references
References 13 publications
4
109
0
1
Order By: Relevance
“…To examine the long-term protection provided by the vaccine, a follow-up study was initiated with the same study cohort, using the identical study design for a period of 8 years [40,41]. 176,078 subjects who received the vaccination between January 2007 and December 2014 at the age of ≥60 years were compared to 528,234 non-vaccinated persons at a ratio of 1:3.…”
Section: Retrospective Cohort Studies For the Evaluation Of The Live mentioning
confidence: 99%
See 1 more Smart Citation
“…To examine the long-term protection provided by the vaccine, a follow-up study was initiated with the same study cohort, using the identical study design for a period of 8 years [40,41]. 176,078 subjects who received the vaccination between January 2007 and December 2014 at the age of ≥60 years were compared to 528,234 non-vaccinated persons at a ratio of 1:3.…”
Section: Retrospective Cohort Studies For the Evaluation Of The Live mentioning
confidence: 99%
“…For this issue it was therefore necessary to combine the results from the SPS study and its follow-up studies (STPS and LTPS) (36,38,39) and to take into account the results of the post-marketing study with members of the Kayser Permanente [41]. The results of the longterm observations show, that the HZ vaccine provides only short term protection against HZ.…”
Section: Conclusion On the Efficacy And Effectiveness Of The Hz Vaccmentioning
confidence: 99%
“…Applying a wane rate of protection in the time equal to that reported by Tseng et al 4 to the vaccine efficacy data for both HZ and PHN, the simulation model has calculated the results shown in Table 5.…”
Section: Wane Of Protection Over Timementioning
confidence: 99%
“…Loss of protection over the time. The study by Tseng et al 4 showed the decline and then the loss of vaccine efficacy against HZ in 8 years. At present, however, no data are available on loss of efficacy against PHN.…”
Section: Alternative Scenariosmentioning
confidence: 99%
See 1 more Smart Citation